Riparina I e Riparina II reduzem a neuroinflamação e as alterações gliais em camundongos submetidos ao modelo de depressão induzida por estresse crônico imprevisível - Sales, Iardja Stéfane Lopes (2023)
Neuroinflammation has been identified as one of the factors related to the pathophysiology of depressive disorders, and the hippocampus has been shown to be one of the main brain areas affected. Although there are several antidepressants available for the treatment of depression, many patients do not respond to conventional pharmacotherapy or experience various adverse effects. Riparin I [(O-Methyl)-N-benzoyl-tyramine] (RIP I) and Riparin II [(O-Methyl)-N-2-hydroxy-benzoyl-tyramine] (RIP II) are substances that showed antidepressant activity in animal models of acute and chronic stress by repeated administration of corticosterone. Thus, the present study aimed to investigate the effect of RIP I and RIP II on neuroinflammation, using the model of depression induced by Chronic Unpredictable Mild Stress (CUMS). For this, male Swiss mice were exposed to stressful events for 28 days and from the 15th day received RIP I or RIP II at a dose of 50 mg/kg or fluoxetine 10 mg/kg or vehicle, orally; one group did not undergo the ECI, in order to be used as a control. On the 29th day, the animals were submitted to behavioral tests to evaluate locomotor activity (Open Field), depressive-like behaviors (Forced Swimming, Preference for Sucrose), social preference (Social Interaction) and cognitive performance (Y Maze and Recognition of the New Object) and then had their brains dissected. The expressions of microglia and astrocytes markers were evaluated and the cytokines TNF-α and IL-Iβ measured in the hippocampus. Furthermore, computational strategies were used to predict protein targets and molecular docking calculations. CUMS induced anxiogenic and depressive-like behaviors, cognitive deficit, high levels of TNF-α and IL-Iβ cytokines, hypoactivation of astrocytes, seen by reduced expression of the GFAP marker and hyperactivation of microglia, with increased expression of the Iba-1 marker, in the hippocampus. These changes were reversed by treatment with RIP I or RIP II, showing their antidepressant, anxiolytic and anti-neuroinflammatory activity. Target prediction and molecular docking suggested NLRP3, ASC and P2X7 proteins as likely targets for RIP I and RIP II. In pharmacokinetic prediction, with analysis of physicochemical properties, RIP I and RIP II proved to be good drug candidates, with good oral availability and ability to cross the blood-brain barrier. RIP I and RIP II are likely inhibitors of isoforms of the liver enzymes CYP1A2 and CYP2D6, but they have not been shown to be substrates for P-glycoprotein. The presented results show the antidepressant potential of RIP I and RIP II, with beneficial effects on behaviors related to anhedonia, social interaction and cognitive performance, facing exposure to chronic stress. This ability is related to the inhibition of inflammatory mechanisms, with emphasis on the ability to reverse damage associated with astrocytic and microglial alterations. The proposed mechanism of action through molecular docking seems to be related to the modulation of the P2X7-NLRP3-IL1β pathway, probably in the NATCH domains of NLRP3, CARD of ASC and P2X7, as corroborated by the changes seen in the activity of glial cells and hippocampal levels of cytokines. RIP I and RIP II proved to be promising compared to the drugs available on the market for the treatment of depression.